Communication correlates of HIV-related self-stigma among individuals at higher risk of HIV exposure in Malaysia - Mehrabi, Davood (2015)
Stigma is a negative label or stereotype about a particular group or an individual who is discredited, isolated, abused or discriminated against. A person stigmatized with HIV is generally excluded or isolated from the society because of the grave infectious disease that he or she has, or is thought to have, but others do not have. HIV-related stigma has been identified as the most important barrier to response against HIV. Although a large volume of research paid attention to HIV-related stigma, little is known about HIVrelated self-stigma among individuals at higher risk of HIV exposure namely female sex workers (FSWs), injecting drug users (IDUs), men who have sex with men (MSM) and transgender individuals (TGs). This study was conducted to determine the correlates of HIV-related self-stigma (HRSS) by utilizing the theory of planned behavior (TPB), a generic theory about human intention and behavior, as the conceptual framework of the analysis. Based on the relevant past studies and informed by this theory, HIV knowledge, age, attitude (towards HIV and people living with HIV), perceived social support, and self-esteem were selected as the potential predictors of HRSS. A self-administered close-ended questionnaire was used to collect the data from 369 individuals at higher risk of HIV exposure (134 FSWs, 95 IDUs, 82 MSM, and 58 TGs). The study used a combination of snowball and respondent-driven sampling methods to approach 456 individuals yielded a response rate of 80.9%. The results revealed that respondents received HIV information frequently from the Internet, television, friends, and newspaper, respectively. Newspaper was rated the most useful source of HIV information followed by television, the Internet and friends. The majority of respondents have a good knowledge of HIV, high self-esteem,favorable attitudes towards both HIV, and people living with HIV. However, attitudes towards HIV were more favorable than attitudes towards people living with HIV. The respondents perceived good social support from a special person, followed by friends and family members. A significant but negative relationship of HIV knowledge, age, attitudes towards HIV,attitudes towards people living with HIV, and perceived social support with HIVrelated self-stigma was found. This study also showed that the relationship between self-esteem and HIV-related self-stigma was not statistically significant. The relationship between HIV knowledge and HIV-related self-stigma was mediated by attitudes towards HIV. However, it was attitudes towards people living with HIV where not found to mediate the relationship between HIV knowledge and HIV-related self-stigma. The results also revealed that age, attitudes towards people living with HIV, perceived social support and attitudes towards HIV collectively explain 20% of the variance in HIV-related self-stigma. Thus, this study advances the understanding by clarifying the relative contribution of these four variables in the variance of HIV-related self-stigma. The findings also emphasize that relying only on increasing HIV knowledge, rather than paying attention to social factors such as social support from different sources such as family members and friends, may not be successful in reducing HIV-related self-stigma.